Reducing the Risks of Nuclear War—The Role of Health Professionals - Chris Zielinski (AlQalam Journal of Medical and Applied Sciences, 2023)
In January, 2023, the Science and Security Board of the Bulletin of the Atomic Scientists moved the hands of the Doomsday Clock forward to 90 s before midnight, reflecting the growing risk of nuclear war [1]. In August, 2022, the UN Secretary-General António Guterres warned that the world is now in “a time of nuclear danger not seen since the height of the Cold War [2]. The danger has been underlined by growing tensions between many nuclear armed states [1,3]. As editors of health and medical journals worldwide, we call on health professionals to alert the public and our leaders to this major danger to public health and the essential life support systems of the planet—and urge action to prevent it.